Why are woody plants fleshy‐fruited at low elevations? Evidence from a high‐elevation oceanic island. (14th October 2018) - Albert, Sébastien; Flores, Olivier; Rouget, Mathieu; Wilding, Nicholas; Strasberg, Dominique
Abstract: Question: The composition of fruit types, fleshy vs dry fruits, greatly influences the functioning of plant communities. Literature documenting spatial patterns of fruit types at fine scale is abundant. However, studies at larger geographical scale remain scarce, especially on high‐elevation oceanic islands that provide a great environmental heterogeneity. Here, we investigated how abiotic factors explained the proportion of fleshy‐fruited species (pFF) on Réunion. We asked (a) which abiotic factors were most related to pFF, (b) if fleshy‐fruited canopy species were more sensitive than fleshy‐fruited shrubs to harsh climatic conditions and (c) what are the relationships between pFF, endemism and phylogenetic relatedness. Location: Réunion (3, 070 m a.s.l), Mascarene archipelago, South‐West Indian Ocean. Methods: We used a dataset of 429 vegetation plots and assigned fruit types, growth forms and geographical distribution to 213 native woody species. Phylogenetic trees were constructed for each plot. We used GLMs to measure the relationship between pFF and abiotic factors, controlling for spatial autocorrelation. We then assessed the relationship between pFF, the standardized net relatedness index and the proportion of endemic species. Results: The top model explained 78% of the variation in pFF. Elevation was by far the best predictor, with pFF decreasing from 81% at 50 m a.s.l to 0% at 3, 000 m a.s.l. At low elevations, pFF was higher on the wet windward (81%) than on the leeward (70%) where phylogenetic clustering was evident. Almost half (48%) of woody plants was fleshy‐fruited trees at low elevations. The proportion of fleshy‐fruited trees declined sharply with elevation and was significantly related to precipitation of the driest month contrary to the proportion of fleshy‐fruited shrubs that showed a hump shaped pattern along elevational gradient and no correlation with precipitation of the driest month. At high elevations, most plant assemblages were phylogenetically clustered and strongly dominated by single‐island endemic dry‐fruited plants. Conclusions: The striking relationship between pFF and elevation, the shift among fleshy‐fruited growth forms along climatic gradients and the phylogenetic clustering of assemblages subjected to harsh climatic conditions, suggested that climatic factors were the main drivers of the distribution of fruit types on Réunion. To explain the absence of fleshy‐fruited species at high elevations, we hypothesized that native fleshy‐fruited lineages lacked the evolutionary potential to adapt and fleshy‐fruited cold‐adapted lineages had major difficulties reaching Réunion. Abstract : The composition of fruit types has never been investigated at landscape scale on oceanic islands. We showed on Réunion a tremendous decrease of the proportion of fleshy‐fruited plants with elevation and a large dominance of radiated dry‐fruited plants in subalpine shrubland. Climatic factors were major drivers, but the lack of cold‐adapted fleshy‐fruited lineages because of biogeographic constraints may strongly influence this pattern.